Implementation of Technology-Based Learning Media in Islamic Religious Education Learning at SMA Stabat - Keisha Putria Daphinta; Basri Basri; Mustamar Iqbal Siregar (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study aims to explore the implementation of technology-based learning media, the obstacles faced by teachers, and the strategies they employ in utilizing such media in Islamic Religious Education (PAI) learning at SMA Stabat. This research uses a descriptive qualitative approach with Islamic Religious Education teachers from SMA Negeri 1 Stabat and SMA Swasta Persiapan Stabat as the subjects. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The findings show that PAI teachers at SMA Negeri 1 Stabat have effectively integrated various digital media such as PowerPoint, instructional videos, YouTube, Quizizz, and Google Classroom to enhance students’ participation and understanding. Meanwhile, teachers at SMA Swasta Persiapan Stabat utilized simpler media such as PowerPoint, offline videos, and audio recordings of Qur’anic recitations (murottal) according to the available resources. The main obstacles in implementation include limited technological facilities, low digital literacy among teachers, and unstable internet connections. To overcome these challenges, teachers participated in training, engaged in self-directed learning, and innovated in using offline-based media.